2016
DOI: 10.1016/j.agee.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat heterogeneity promotes soil fertility and ground-dwelling arthropod diversity in Mediterranean wood-pastures

Abstract: Mediterranean wood-pastures are extensive agroforestry systems that hold great ecological, social and cultural values, which consist of mixtures of grassland, scattered trees and shrubs, primarily used for livestock grazing. For centuries, low-intensity management in these landscapes has resulted in multiple microhabitats that favour biodiversity and are considered key elements for the long-term persistence of wood-pastures. However, the relative contribution of each microhabitat type to wood-pasture biodivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…Sparse woody vegetation is of crucial importance for the overall biodiversity of pastures [ 7 ], [ 8 ], [ 11 ], [ 12 ] ( Table 4 ) and contributes to the soil fertility [ 14 ]. Still, this vegetation elements are not explicitly recognized by major policies and institutions responsible for the governance of the management of the pastoral systems [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sparse woody vegetation is of crucial importance for the overall biodiversity of pastures [ 7 ], [ 8 ], [ 11 ], [ 12 ] ( Table 4 ) and contributes to the soil fertility [ 14 ]. Still, this vegetation elements are not explicitly recognized by major policies and institutions responsible for the governance of the management of the pastoral systems [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Solitary trees on pastures significantly increased the overall diversity of lichens [ 9 ], vascular plants and bryophytes [ 10 ]. Sparse trees are important breeding sites for birds [ 11 ], [ 12 ] and they may also harbor a great invertebrate diversity [ 13 ], [ 14 ]. Trees create a distinct microclimatic conditions on grasslands and this results in distinct arthropod species assemblages, including several rare species [ 15 ], [ 16 ], [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, we observed that vegetation heterogeneity can indirectly affect the soil macro-arthropod communities by altering the soil fertility and soil texture. García-Tejero and Taboada have shown that vegetation heterogeneity enhanced the soil fertility and the decomposition process, and increased the contents of available nutrients [34]. A large amount of available nutrients could potentially promote plant growth, as well as supply sufficient food, and thus enhance the abundance, richness and diversity of soil macro-arthropods.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of trees on open grasslands is also a positive factor for diversity in ants [43,44], coleoptera and diptera [45][46][47][48][49]. Ant species richness and Shannon diversity tend to increase in areas under Q. rotundifolia canopies as a consequence of the shade effect, as tree size plays an important role in the density of ground ant nests.…”
Section: Tree Factormentioning
confidence: 99%